The Effects of Maternal Dietary Supplementation of Cholecalciferol (Vitamin D3) and 25(OH)D3 on Sow and Progeny Performance - M. T Thayer; J. L. Nelssen; A. J. Langemeier; J. Morton; J. M. Gonzales; S. R. Kruger; Z. Ou; A. J. Makowski; J. R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 69 sows (DNA Line 200 × 400) and their progeny were used to determine if feeding a combination of vitamin D3(Rovimix D3, 500,000 IU/g; DSM Nutritional Products, Parsippany, NJ) and 25(OH)D3(Hy-D, DSM Nutritional Products, Parsippany, NJ) influences neonatal and sow vitamin D3 status, muscle fiber morphometrics and development of the piglets, and subsequent growth performance to market. Within 3 days of breeding, sows were allotted to 1 of 3 dietary treatments fortified with 680 IU/lb vitamin D3(CON), 227 IU/lb vitamin D3+ 11.3 μg/lb 25(OH)D3(DL), or 680 IU/lb vitamin D3+ 22.7 μg/lb 25(OH)D3(DH). Differences in sow productivity and growth performance of progeny due to dietary treatment were not observed (P>0.050). When pigs were sacrificed at birth, there were no treatment effects for all fiber morphometric measures (P>0.170), except primary fiber number and the ratio of secondary to primary muscle fibers (P<0.016). Pigs from CON fed sows had fewer primary fibers than pigs from sows fed the DH treatment (P= 0.014), with pigs from sows fed DL treatment not differing from either (P>0.104). Pigs from the CON and DL fed sows had a greater secondary to primary muscle fiber ratio compared to pigs from DH sows (P<0.022) but did not differ from each other (P= 0.994). There were treatment × time interactions for all sow and pig serum metabolites (P<0.001). Therefore, we further compared treatment means within time period. At all time periods, sow serum 25(OH)D3concentrations differed for all treatments with the magnitude of difference largest at weaning (P<0.011). On all three collection days, DH fed sows contained the greatest serum levels of 25(OH)D3. For pig vitamin D3status at birth, the interaction was because serum concentrations of 25(OH)D3in pigs from sows fed CON and DL were not different from each other. But at weaning, pigs from all sow treatments differed. At both sampling days, progeny from DH fed sows contained the greatest serum levels of 25(OH)D3. There was no interaction for 25(OH)D3concentration in colostrum and milk; however, a main effect of dietary treatment (P<0.001) and of time (P= 0.001) existed. Within maternal dietary treatment, colostrum collected within 12 h contained less (P= 0.001) 25(OH)D3compared to milk collected on d 21. Within sampling time, 12 h for colostrum and 21 d for milk, sows from all treatments were different (P<0.030), with the largest 25(OH)D3concentration from DH fed sows, followed by DL and then CON. In conclusion, combining vitamin D3and 25(OH)D3in the maternal diet improves the vitamin D3status of the dam and progeny and it increases primary muscle fibers at birth.
Keywords: vitamin D; sows; 25(OH)D3